2019
DOI: 10.3390/ma12203308
|View full text |Cite
|
Sign up to set email alerts
|

Simple In-House Fabrication of Microwells for Generating Uniform Hepatic Multicellular Cancer Aggregates and Discovering Novel Therapeutics

Abstract: Three-dimensional (3D) cell culture models have become powerful tools because they better simulate the in vivo pathophysiological microenvironment than traditional two-dimensional (2D) monolayer cultures. Tumor cells cultured in a 3D system as multicellular cancer aggregates (MCAs) recapitulate several critical in vivo characteristics that enable the study of biological functions and drug discovery. The microwell, in particular, has emerged as a revolutionary technology in the generation of MCAs as it provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 43 publications
(53 reference statements)
1
15
0
Order By: Relevance
“…Compared with the aforementioned traditional 2D culture systems, in vitro three-dimensional (3D) culture systems [16,17] may better recapitulate the cell-cell and cell-matrix interactions occurring in LF tissue [18]. However, although 3D culture systems have been widely applied in many disease models, such as cancer [19][20][21] cardiovascular disease [22] and wound healing [23], limited information regarding in vitro 3D LF models is available. Given that clinical observations of LFH tissue have revealed that elastic fibers decrease and degenerate while collagen increases in hypertrophic tissue [24] developing a pure cell model without adding the extracellular matrix (ECM) could help us understand the changes in the ECM composition over time.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the aforementioned traditional 2D culture systems, in vitro three-dimensional (3D) culture systems [16,17] may better recapitulate the cell-cell and cell-matrix interactions occurring in LF tissue [18]. However, although 3D culture systems have been widely applied in many disease models, such as cancer [19][20][21] cardiovascular disease [22] and wound healing [23], limited information regarding in vitro 3D LF models is available. Given that clinical observations of LFH tissue have revealed that elastic fibers decrease and degenerate while collagen increases in hypertrophic tissue [24] developing a pure cell model without adding the extracellular matrix (ECM) could help us understand the changes in the ECM composition over time.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid CO 2 laser prototyping has been previously demonstrated as an effective alternative for the fabrication of microwells for the formation of size-controlled 3D spheroids [ 3 , 11 , 13 , 16 ]. However, one major obstacle that has remained non-demonstrated in PS microwells is the inevitable loss of cells after cell seeding because of the required washing step to ensure that cells are not lodged into the microwells and can be efficiently removed without perturbing the size-uniformity of the MCTSs [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, choosing PS as the microwell substrate is favorable from a biologist’s perspective because PS is the most commonly utilized plastic for in vitro cell culture research. Compared to PDMS [ 28 ] or polyester [ 13 ] microwells, PS is hassle-free for the researchers in terms of the material accessibility, and more amenable in terms of compatibility with different forms of conventional culture plasticwares, such as Petri dishes [ 3 ] or microtiter plates [ 16 ]. In addition, the PS microwell displayed a gentle concave bottom, and curved microwell structures have been reported to promote the aggregation of spheroids [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations